Metacarpal fractures in children (literature review) - S. U. Semenov; N. G. Zhila; K. M. Komarov; P. B. Komarov (Вестник хирургии имени И.И. Грекова)
Hand injury holds one of the first places among injuries of the musculoskeletal system in children. The share of fractures of metacarpal bones account for 10 to 35 % of all fractures, while for 1/5 of pediatric patients they are accompanied by injury to the growth plate. The existing classification of pediatric metacarpal fractures does not accurately reflect the nature and extent of damage to the growth plate; it underestimates or overestimates the nature of the fracture, the degree of displacement of fragments of metacarpal bones with the traditional approach to treatment, without taking into account the age-related anatomical and physiological characteristics of the traumatized child. Further scientific research on the diagnosis and treatment of traumatic injuries of metacarpal bones in children, the introduction of the results of these studies into clinical practice will contribute to improving the quality of care for patients with hand injuries and to preventing disability of the children.